Petrography and the REE-composition of apatite in the Paleoproterozoic Pilgujärvi Sedimentary Formation, Pechenga Greenstone Belt, Russia. (1st August 2016) - Joosu, Lauri; Lepland, Aivo; Kreitsmann, Timmu; Üpraus, Kärt; Roberts, Nick M.W.; Paiste, Päärn; Martin, Adam P.; Kirsimäe, Kalle
Abstract: The first globally significant phosphorous-rich deposits appear in the Paleoproterozoic at around 2 Ga, however, the specific triggers leading to apatite precipitation are debated. We examine phosphorous-rich rocks (up to 8 wt% P2 O5 ) in 1.98–1.92 Ga old Pilgujärvi Sedimentary Formation, Pechenga Greenstone Belt, Russia. Phosphates in these rocks occur as locally derived and resedimented sand-to-gravel/pebble sized grains consisting of apatite-cemented muddy sediments. Phosphatic grains can be subdivided into four petrographic types (A–D), each has a distinct REE signature reflecting different early-to-late diagenetic conditions and/or metamorphic overprint. Pyrite containing petrographic type D, which typically has a flat REE pattern, negative Ce anomaly and positive Eu anomaly, is the best preserved of the four types and best records conditions present during apatite precipitation. Type D phosphatic grains precipitated under (sub)oxic basinal conditions with a significant hydrothermal influence. These characteristics are similar to Zaonega Formation phosphates of NW Russia's Onega Basin, and consistent with phosphogenesis triggered by the development of anoxic(sulfidic)–(sub)oxic redoxclines at shallow sediment depth during the Paleoproterozoic.